Опасность предельного уровня: [роман] / Сергей Самаров - Самаров Сергей Васильевич (Спецназ. ГРУ, 2007)
Экземпляры: ф.23 (2007) / Инвентарный номер: 51555 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44